Multitenancy in Single Instance of Data Persistence Service for Supporting Low-Code Platforms - Julio Gustavo Costa; Luiz Marcos Garcia Goncalves; Samuel Xavier-de-Souza (IEEE Access)
Corporate digitalization, especially among Small and Medium Enterprises, has led to a significant increase in the demand for scarce professionals with expertise in the IT area, especially in Web Information Systems area. On the other hand, concerns about high levels of resource idleness in the cloud are constant. In this scenario, Low-Code Platforms have gained traction in the software industry, whose most commonly found service is the automation of code generation to perform data persistence tasks driven by data models. This approach, however, implies a mode of operation that is not the most mature among cloud computing providers, implying for each model a service instance running on the provider side. Here, we propose a data persistence service for these platforms that avoids code generation, since it interprets data models at runtime and operates in multi-tenant mode with a single service instance. This approach improves resource sharing, mitigating resource idleness within the platform. In addition, we present experiments to support the technical feasibility of the proposed approach. The proposed solution offers an alternative to code generation methods, with the potential to optimize resource utilization while preserving the flexibility to adapt to changes in data models as business needs evolve.